Oxygen-isotope heterogeneity in the Northwest Africa 3358 (H3.1) refractory inclusions − Fluid-assisted isotopic exchange on the H-chondrite parent body. (1st August 2020) - Ebert, Samuel; Nagashima, Kazuhide; Krot, Alexander N.; Bischoff, Addi
Abstract: The nature of oxygen-isotope heterogeneity in refractory inclusions [Ca, Al-rich inclusions (CAIs) and amoeboid olivine aggregates (AOAs)] from weakly metamorphosed chondrites is one of the outstanding problems in cosmochemistry. To obtain insights into possible processes resulting in O-isotope heterogeneity of refractory inclusions, we investigated the mineralogy, petrology, and oxygen isotopic compositions of six CAIs and two AOAs and aqueously formed fayalite grains within the matrix of the H3.1 chondrite Northwest Africa (NWA) 3358. Most of the refractory inclusions studied appear to be unmolten solar nebula condensates; some may have experienced partial melting and/or high-temperature annealing. The NWA 3358 refractory inclusions nearly completely avoided metasomatic alteration on the H-chondrite parent body: nepheline grains replacing anorthite and/or melilite are either very minor or absent. Five out of eight refractory inclusions studied have heterogeneous O-isotope composition: Δ 17 O ranges from ∼− 25‰ to ∼3.5 ± 2‰ (2σ). This O-isotope heterogeneity appears to be mineralogically controlled with melilite and anorthite being systematically 16 O-depleted compared to hibonite, spinel, Al, Ti-diopside, and forsterite all having similar solar-like Δ 17 O of ∼−24 ± 2‰. In contrast to NWA 3358 refractory inclusions, the previously studied AOAs and a fine-grained CAI from the LL3.00 chondrite Semarkona have uniform Δ 17 O of ∼−25‰ (Itoh et al., 2007; McKeegan et al., 1998 ). Because the mineralogically-controlled O-isotope heterogeneity in refractory inclusions from ordinary chondrites appears to correlate with petrologic type of a host meteorite experienced by aqueous alteration, we suggest O-isotope exchange in NWA 3358 CAIs and AOAs resulted from aqueous fluid-rock interaction on the H-chondrite parent asteroids. This is supported by the presence of 16 O-depleted anorthite (Δ 17 O ∼ 3.5 ± 2‰) and aqueously formed fayalite similar depleted in 16 O (Δ 17 O ∼ 4 ± 2‰). The Δ 17 O of NWA 3358 fayalite is comparable to that of magnetite and fayalite in Semarkona and other weakly metamorphosed L3 and LL3 chondrites (Choi et al., 1998; Doyle et al., 2015 ) suggesting similar Δ 17 O of aqueous fluids on the H, L, and LL chondrite parent asteroids.